2017
DOI: 10.1597/16-026
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study to Determine the Reference Plane of Patients with a Unilateral Cleft Lip and Palate

Abstract: It was confirmed that the midsagittal reference planes from these selected landmarks for UCLP patients were compatible with symmetric midsagittal reference planes from the Procrustes analysis and the asymmetric measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The construction of optimal facial planes based on landmarks that are minimally affected by facial asymmetry is a fundamental step for the clinical evaluation of facial asymmetry. In this regard, Kim et al [ 36 ] suggested that the landmark-based reference plane was compatible with reference planes from Procrustes analysis. Therefore, for the present study, we defined reference planes on the basis of the landmark-based technique.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The construction of optimal facial planes based on landmarks that are minimally affected by facial asymmetry is a fundamental step for the clinical evaluation of facial asymmetry. In this regard, Kim et al [ 36 ] suggested that the landmark-based reference plane was compatible with reference planes from Procrustes analysis. Therefore, for the present study, we defined reference planes on the basis of the landmark-based technique.…”
Section: Discussionmentioning
confidence: 98%
“…Increasing the number of patients may be required to delineate the results. Finally, although the landmark-based method for reference plane estimation has been shown to be comparable with semiautomatic and automatic techniques [ 36 ], errors related to the manual digitization of landmarks may exist, since digitization depends upon the ability of the observer to identify them precisely. However, the intraobserver reliability was excellent for the landmarks used in the current study.…”
Section: Discussionmentioning
confidence: 99%